2019
DOI: 10.1093/milmed/usy283
|View full text |Cite
|
Sign up to set email alerts
|

Sweating the Little Things: Tourniquet Application Efficacy in Two Models of Pediatric Limb Circumference

Abstract: Background Current military recommendations include the use of tourniquets (TQ) in appropriate pediatric trauma patients. Although the utility of TQs has been well documented in adult patients, the efficacy of TQ application in pediatric patients is less clear. The current study attempted to identify physical constraints for TQ use in two simulated pediatric limb models. Methods Five different TQ (Combat Application Tournique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Previous reviews of adult and pediatric literature identified experimental studies of tourniquet use in pediatric models such as polyvinyl chloride pipes that demonstrated failure of adult tourniquets on smaller pipes. 397…”
Section: First Aidmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reviews of adult and pediatric literature identified experimental studies of tourniquet use in pediatric models such as polyvinyl chloride pipes that demonstrated failure of adult tourniquets on smaller pipes. 397…”
Section: First Aidmentioning
confidence: 99%
“…Previous reviews of adult and pediatric literature identified experimental studies of tourniquet use in pediatric models such as polyvinyl chloride pipes that demonstrated failure of adult tourniquets on smaller pipes. 397 In making this recommendation, the First Aid Task Force weighed the lack of direct evidence to show that tourniquets are a lifesaving intervention for lifethreatening extremity bleeding in children against the previously established role of a manufactured windlass tourniquet in reducing mortality in adults with life-threatening extremity bleeding. 391 The Combat Application Tourniquet Generation 7 was the specific brand of windlass rod tourniquet used in both included studies, and the minimum limb circumference of the children included was 13 cm.…”
Section: Justification and Evidence-to-decision Framework Highlightsmentioning
confidence: 99%
“…A second study 213 enrolled children 2 to 7 years of age undergoing elective orthopedic surgery, reporting successful application of the C-A-T GEN 7 in all 24 children (11 upper extremities and 13 lower extremities) with a 100% success rate in occluding distal pulses down to a minimal limb circumference of 13 cm. Two studies using models or manikins 210,211 reported that elastic type tourniquets (SWAT-T [H&H Medical Corporation, Williamsburg, Virginia] and R.A. T.S. [RATS Medical, Salt Lake City, Utah]) and pediatric-specific ratcheting tourniquets were the designs capable of tightening on the smallest models (to a circumference of 11.9 cm for the CRMT [M2 Inc, Colchester, Vermont] and R.A.T.S.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Use of other tightening mechanisms, such as ratcheting tourniquets, has been suggested for use in children, but the evidence is lacking. No evidence from human studies was available for other tourniquet mechanisms, however, indirect evidence is available from three experimental studies that evaluate tourniquets in models representing a small limb diameter [16][17][18]. While these studies evaluate a broader range of tourniquet mechanisms, including ratcheting and elastic wrap, the experiments were conducted on manikins and in models using PVC pipe and stair rails and were excluded by our initial search strategy.…”
Section: Discussionmentioning
confidence: 99%